The source of power of the Dayak Ma’anyan Tribes’ political thought and its influence on the elites - Kisno Hadi (Masyarakat, Kebudayaan dan Politik, 2019)
This article describes the political thoughts of power and authority, especially concerning sources of energy and its influences, in the elite group of the Dayak Ma’anyan tribe. Dayak Ma’anyan linked to the Nan Sarunai Kingdom, which was a sovereign country in the politic, economy, social and cultural scope in the 14th century. It collapsed because of the Majapahit military intervention. The elites’ political thoughts highly influence the source of power in Nan Sarunai in the current era in local political practices. This article employed the descriptive, explanatory method paired with descriptive interpretative data analysis and enriched by in-depth interview to 10 informants. The analysed unit was an elite group of Dayak Ma’anyan in the Barito Timur Regency. The research discovered there to be two sources of power. First, there is procedure power, i.e. Adat (customary law), and second, there is substantial power, i.e. 1) Alatala (God) and Nanyu (gods or ancestry); 2) Tutur or Hurui (genealogy); 3) Panatau (treasuries) and 4) Pusaka Keagungan (symbols of power). These sources are the main influences of usable power, e.g. in the emerging of the East of Barito regency in 2002, in ethnic identity within the context of bureaucracy and elections. The data derived from in-depth interviews, Taliwakas (stories about local leader), Hiyang Wadian (sacred song of the priest in ritual), Sorosilah (stories on the histories of leaders) and the customary law of Dayak Ma’anyan. The data interpretation was based on the theory of traditional power by Benedict Anderson and the theory of the source of power by Charles F. Andrain.